Schistosoma japonicum extracellular vesicle proteins serve as effective biomarkers for diagnosing parasite infection - Huixin Wu; Bikash R. Giri; Bikash R. Giri; Huimin Li; Yameng Zheng; Xiaoli Yan; Guofeng Cheng (Frontiers in Cellular and Infection Microbiology, 2024)
Schistosoma species are the causative agent of schistosomiasis and shows worldwide distribution. There is a great need to develop a sensitive diagnostic approach for controlling the disease. Previously, we identified large numbers of Extracellular Vesicle (EV) proteins from Schistosoma japonicum (S. japonicum), but rarely these proteins have been evaluated for their diagnostic potential. In the present study, we performed bioinformatic analyses of S. japonicum identified EV-associated proteins from the previous study and then identified Schistosoma-specific proteins with potentially secreted capability. Among them, we selected SJCHGC02838 protein, SJCHGC05593 protein, SJCHGC05668 protein and a hypothetical protein (SJHYP) to evaluate their diagnostic potential for detecting S. japonicum infection. First, we determined the expression of these four proteins at the transcript levels using qRT-PCR and revealed that all these genes showed higher expression in adult stage. Then, we cloned the full-length cDNA for each protein into a prokaryotic expression vector and successfully generated the recombinant proteins. Upon the purification of recombinant proteins, we developed an indirect ELISA method to evaluate the diagnostic potential of these purified recombinant proteins. The results showed high sensitivity for detecting Schistosoma infection. Additionally, these proteins also displayed a good potential for detecting Schistosoma infection, especially SJCHGC05668 protein at an early stage. The diagnostic potentials of these recombinant proteins were further evaluated by Western blot and comparatively analyzed by our previously developed cfDNA methods.